Determination of mTOR complex influence in ribosomal protein transport under amino acid starvation condition (Experimental biology, 2015)
Synthesis of ribosomal proteins controlled by regulation of many processes in cells. Role of mTOR pathway in ribosomal protein transport is coordinating of nucleocytoplasmic transport which depends on nutrient availability. In our research we have detected low abundance of ribosomal proteins rpS3 and rpL26 in prenuclear and nuclear fraction ofMEF cells. In addition, same decreasing level of ribosomal protein in Rictor null cells compared to control cells indicates that mTORC2 does not involve in ribosomal biogenesis. Character of decreasing of ribosomal protein in nuclear fraction by time points explained that this process is regulated by activity of mTOR protein kinase.
Keywords: ribosomal proteins; mTOR; sub-cellular fractionation.